BLEOMYCIN-INDUCED FLAGELLATE DERMATITIS: A CASE REPORT - Walfrido Bispo Junior; Rosane Soares Oliveira; Silvana Maria Barros de Oliveira; Monik Kelly Santos Lima (Universidade Federal do Paraná, 2015)
Flagellate Dermatitis consists of cutaneous hyperpigmentation with a flagellate appearance, one specific cause of which is bleomycin. Bleomycin is a chemotherapy agent used in the treatment of different neoplasias. This report's objective is to describe the case of a 31-year-old patient receiving treatment for Hodgkin Lymphoma with a protocol of Antineoplastic Chemotherapy made up of four drugs, including bleomycin, which led to the development of Flagellate Dermatitis. This is a report of a case which took place in a teaching hospital in the Northeast of Brazil in 2014. The therapy used as treatment was use of corticosteroid, which led to the remission of the lesions of the flagellate type and allow the continuation of the treatment without the need for changing the chemotherapy protocol. The study's importance lies in that it raises discussion regarding the aspects involving the management of this hypersensitivity so as to ensure the continuity of the antineoplastic treatment.